Debt management for development : protection of the poor and the millennium development goals - Raffer, Kunibert (Cheltenham Edward Elgar Publishing Ltd.)
From the British Library catalogue: "Raffer discusses the international debt problem in a profound way and his proposal, the Raffer proposal, is ingenious, practical and wise."
1. Brief history of debt management until 1989 - 2. Briefhistory of debt management after 1989 - 3. In Quest of solutions: sovereign insolvency proposals, collective action clauses and recent country cases -- 4. Gleneagles, the multilateral debt relief initiative and the US crisis -- 5. The Raffer proposal: an international chapter 9 for countries -- 6. Debtor rights and fairness to creditors in rule of Law-based insolvency systems - 7. MDGs, debt distress and poverty: theoretical roots of policies protecting the poor in debtor countries - 8. Poverty, debtor protection and the MDGs - 9. Debt distress, global public goods and a global development; partnership - 10. NGO advocacy for debt reduction cum debtor protection - 11. The Concept of sustainability of international financial institutions - 12. Problems of overoptimism and ownership - 13. MDGs and preferred creditor status - 14. Lending or granting: ODA and the MDGs
Includes bibliographical references (p.278-295) and index.
Keywords: Public finance; EXTERNAL DEBT; DEBT RELIEF; DEVELOPING COUNTRIES; ECONOMICS